A Multi-Objective Optimization Model for Planning Unmanned Aerial Vehicle Cruise Route. (7th June 2016) - Liu, Xiaofeng; Gao, Limei; Guan, Zhiwei; Song, Yuqing; Zhang, Rui
The use of unmanned aerial vehicles (UAVs) was introduced to monitor a traffic situation and the respective cruise route optimization problem was given. Firstly, a multi-objective optimization model was proposed, which considered two scenarios: the first scenario was that there were enough UAVs to monitor all the targets, while the second scenario was that only some targets could be monitored due to a lack of UAVs. A multi-objective evolutionary algorithm was subsequently proposed to plan the UAV cruise route. Next, a route planning experiment, using the Microdrones md4-1000 UAV, was conducted and a UAV route planning case was studied. The experiment showed that the UAV actual flight route was almost consistent with the planned route. The case study showed that, compared with the initial optimal solutions, the optimal total UAV cruise distance and the number of UAVs used in scenario 1 decreased by 41.65% and 40.00%, respectively. Meanwhile, the total UAV cruise distance and the number of targets monitored in scenario 2 reduced by 15.75% and increased by 27.27%, respectively. In addition, a comparison study with other algorithms was conducted, while the optimization results were also improved. This demonstrated that the proposed UAV cruise route planning model was effective.